An in-vitro study to compare antimicrobial activity of endodontic sealers - Ariffin, Zaihan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Complete elimination of microbes in teeth with an infected dental pulp is one of the main objectives of endodontic treatment. Endodontic sealers should have a wide antimicrobial spectrum and action time because of the polymicrobial characteristics of endodontic infections and to eliminate residual microorganisms unaffected by the effects of chemomechanical preparation and intracanal medication of endodontic treatment.